Exploring the influence of takotsubo syndrome on oncologic patients’ mortality - Tini, Giacomo; Arcari, Luca; Sclafani, Matteo; Spallarossa, Paolo; Camastra, Giovanni; Battistoni, Allegra; Autore, Camillo; Volpe, Massimo; Musumeci, Beatrice; Ameri, Pietro; Cacciotti, Luca (Frontiers in Cardiovascular Medicine, 2022)
It has been reported that patients affected by takotsubo syndrome (TTS) with a concurrent diagnosis of cancer suffer from greater mortality as compared to their non-cancer counterpart. It remains unclear whether TTS worsens the prognosis of cancer patients as well. Aim of this study was to compare outcomes of cancer patients with and without TTS. We combined data from two independent cohorts: one consisted of a prospective multicentre TTS registry; the second cohort consisted of all oncologic patients from two Cardio-Oncology Outpatient Clinics, who did not have cardiovascular conditions at the time of the cardio-oncologic visit. From the TTS registry, we selected patients with cancer (cancer-TTS patients). Next, we matched these patients with those from the cardio-oncologic cohort (cancer non-TTS patients) in a 1:2 fashion by age, sex and type and cancer staging. Study endpoint was all-cause mortality. Among 318 TTS patients, 42 (13%) had a concurrent diagnosis of cancer. Characteristics of cancer-TTS patients and of the 84 matched cancer non-TTS subjects were comparable with the exception of diabetes mellitus, which was more common in cancer non-TTS patients. All-cause mortality was similar between cancer-TTS and cancer non-TTS patients. At Cox regression analysis TTS was not associated with mortality (OR 1.4, 95%CI 0.6-3.3, p=0.43). Our findings show that even in the presence of acute heart failure due to TTS, the prognosis of oncologic patients is driven by the malignancy itself. Our results may prove useful for integrated management of cardio-oncologic patients.